Scene Barrier Effects on Vehicle Deceleration Rate during Primary Accident in a Suburban Area - Rani, M.F.H.; Abu Bakar, S.; Hashim, M.S.M.; Harun, A.; Razlan, Z.M.; Wan, W.K.; Zunaidi, I.; Ibrahim, I.; Afendi, M.; Efi, N.E.; Ahmad, Y.; Dalib, M.; et al. (Journal of the Society of Automotive Engineers Malaysia, 2021)
This study uses a simulation of primary accident to investigate the scene barrier effects on vehicle deceleration rate in the suburban area to assess driver behaviour. Several conditions were designed and experimented to determine the capability of scene barrier, which included free flow traffic without an accident, an accident without scene barrier and an accident with scene barrier. The vehicle deceleration rate was investigated by collecting speed-time data in normal traffic zone and rubbernecking zone. Results found that the average vehicle deceleration rate reached as high as - 1.93 km/h/s in rubbernecking zone compared to normal traffic zone (as high as - 0.49 km/h/s) especially when an accident was simulated without the scene barrier. Introduction of scene barrier during the simulated accident improved traffic flow and reduced rubbernecking phenomena by improving the average vehicle deceleration rate in rubbernecking zone by up to 43.0 %. However, sudden deceleration cannot be totally eliminated during the simulated accident with the scene barrier due to driver behaviour. For optimization of braking time during a primary accident, a study of the algorithm of Autonomous Emergency Braking (AEB) system is necessary.